Young People as Suppliers on The Social Media Sharing Market On the Example of Social Economy Students - Iwona LUPA-WOJCIK (Communications of International Proceedings, 2022)
The sharing economy is a trend that has been systematically developing for years, especially in times of crisis. In turn, social media are platforms that can facilitate this type of transaction. On the one hand, they ensure speed in finding people interested in obtaining goods on the second hand market. However, on the other hand, they can become a source of potential dangers. The purpose of this article is to determine the popularity of the social media sharing trend among young people as suppliers on the example of social economy students. The main hypothesis states that social economy students are mostly active participants in the social media sharing trend as providers. As a research method was used the survey. The research was carried out on first-year students of the social economy of the Pedagogical University of Krakow. The analysis showed that social economy students are mostly not active participants in the social media sharing trend as providers. It turns out that the lack of knowledge about it is quite common among them.
Keywords: sharing economy; social media; social media sharing